KS-TVET Life Skills Course Progress Report - El-Serafy, Yomna; Klune, Christopher (Open Development & Education, 2023)
An output of the Open Development & Education, https://.opendeved.net/
ZenodoArchiveID: 8413609 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1022 ZenodoArchiveConcept: 8413608
Keywords: _comingsoon; _r:AddedByMyEducationEvidence